Método comunicacional del sistema de vacunación en Ecuador - López Nivela, Aldo Andrés (2023)
In this research work, the analysis of the Communication Plan used for the 9/100 Vaccination Plan campaign was carried out in order to know how the reception of information to the target audience of this campaign was handled. In order to carry out this research, theoretical information was taken in order to obtain knowledge of how a communication plan is managed, the most important strategies, the management of online and offline information, and how the plan was designed by the Ministry of Public Health in conjunction with the National Government. After defining the research approach, qualitative and quantitative data collection instruments were used, therefore, it is mixed, which served to obtain information with specific data and the definition of better corroborated information..........